The rise and fall of religion: An agent-based model of secularisation, security and prosociality - Puga-Gonzalez, Ivan; Shults, F. LeRon; Gore, Ross; Talmont-Kaminski, Konrad (PLOS ONE, 2025)
The relationship between religion, society, and individual behaviour has been a subject of extensive inquiry, drawing upon a rich collection of historical and contemporary perspectives. The scientific study of religion at the social level has often found its roots in the foundational work of Durkheim (Durkheim, 1912), who posited that religion serves as a catalyst for social order and the promotion of prosocial behaviour. At the same time, Malinowski’s observations regarding the connection between ritual and anxiety have led to a number of lines of inquiry that have come to extend to other aspects of religion. Yet, taken together, these two approaches create friction by simultaneously linking religion to low and high levels of environmental threats and anxiety. This becomes particularly relevant in discussions of secularisation in general and existential security in particular. This study embarks on a theoretical exploration of these approaches, connecting them through an agent-based computer simulation. By linking together some of the intricate mechanisms that underlie the dynamics of religion, prosociality, and anxiety, we aim to shed light on the conditions that give rise to highly religious societies and the subsequent decline in religiosity, with a view to the significance of central institutions that ensure cooperation without recourse to religion in this complex narrative.